Physical variables - lake profile manual sample from Stortjärn, platform - Svartberget Research Station (Swedish University of Agricultural Sciences, 2025)
Manual measurements of physical parameters are taken at the deepest spot of the SITES Water lakes on a (bi-)weekly basis during ice-free conditions, and on a monthly basis in the presence of ice.
Svartberget Research Station (2025). Physical variables - lake profile manual sample from Stortjärn, platform, 2017-01-10–2025-09-16 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/b_C8jkZap-eisSP9V1UPxYUY
Keywords: Svartberget Research Station; Oxygen; Time instant; Time instant; Water temperature; Water temperature; Dissolved oxygen; Dissolved oxygen; Oxygen saturation; Oxygen saturation; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap